Insurance Utilities in Indonesia: A Study for Future Opportunities - Ingrid Green Nego; Dika Oktaviani Yustedjo; Hotmada Parlindungan; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2025)
This study analyzes Indonesia's path toward universal health coverage (UHC), which has been marked by the introduction of targeted schemes such as Askeskin and Jamkesmas, culminating in the comprehensive National Health Insurance (JKN) program. This literature review systematically synthesizes peer-reviewed empirical studies published between 2005 and March 2025, examining the impact of government-managed health insurance on healthcare utilization, financial protection, and equity across different population groups. The study conducted a structured narrative synthesis of studies retrieved from PubMed, Scopus, Web of Science, and Google Scholar, focusing on inpatient and outpatient services, maternal and dental care, and out-of-pocket expenditures. The findings indicate that insured individuals consistently demonstrate higher utilization rates and significant reductions in out-of-pocket spending, with notable benefits in maternal health and primary care in rural areas; however, geographic and socioeconomic disparities persist, particularly among the urban poor and remote communities. Secondary analysis revealed moral hazard effects and shifting private market dynamics, highlighting the need for cost-sharing mechanisms and regulatory oversight. Propose policy strategies to expand enrollment, adjust premium subsidies, integrate fragmented schemes, strengthen the community health center (Puskesmas) infrastructure, and enhance preventive care and health literacy. An integrated approach aligning financial, clinical, and regulatory reforms is essential to optimize equity, efficiency, and sustainability in Indonesia’s UHC journey.